RESPONSE OF ABELMOSCHUS ESCULENTUS L. FORINOCULATION WITH MYCORRHIZAE AND FOLAIR APPLICATION WITH BIO-STIMULATORS AND EFFECT ON VEGETATIVE GROWTH CHARACTERS - & et al., AL-Samarai (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study  was carried out at the Fields belongs of Horticulture  Department, Collage of Agricultural Engineering Science, University of  Baghdad, Al-Jadiriyah for the spring season 2016 -2017 to study the effect for  inoculation mycorrhizae and  folair application  with bio stimulators and their interaction in the growth characters of  (local okra  ptera). A factorial experiment  (2  in randomized complete block design (RCBD), the experiment included (12) treatment  Distributed  in three  replicates. The three factors used in this experiment included . The inoculation with control (C) Mycorrhizae  ( M ) , Biozyme  (B ) ( B1 2cm3.L-1), ( B2 4cm1-.L-1) , Phosphalas (P) (P 2cm3.L-1),  ( M + B1), ( M + B2), (P + M ), ( P + B1), (P + B2), ( M + P + B1), ( M + P + B2). The data were analyzed according to the design followed and the mean was tested by the lowest significant difference at 0.05%. The results showed a significant increase in the studied traits .  The results showed that the three factors and their interactions had significant effects on most of the growth characters measured. The inoculation with the Mycorrhizae  , Biozyme  and  Phosphalas was superior in giving higher values of  plant height  (M1B2P1) 120.00 cm,  Main branches number  per plant 13.00,  number of  leaves 197.0  (Leaf .plant -1),  leaf area  394.0 (dcm2. Leaf ),  fresh weight  of vegetative 3200 (kg. plant-1)  Dry weight of vegetative 209.0 ( g . plant-1), number of  nodules on the stem 41.33  (nod. plant -1),  relative chlorophyll content  (SAPD) respectively. The M1B2P0 combination treatment recorded the highest values of  secondary branches number  per plant 10.33. The M1B1P0 treatment recorded the highest values of diameter of stem 4.03 (cm).